Surgical Management of Perforated Duodenal Ulcers: A Clinical and Operative Outcome Analysis - Xayitov U. X (American Journal of Biology and Natural Sciences, 2025)
Perforated duodenal ulcer remains one of the most severe complications of peptic ulcer disease, often presenting as an acute surgical emergency associated with significant morbidity and mortality if not promptly diagnosed and treated. The standard approach to treatment has evolved over the decades, moving from open laparotomy to minimally invasive techniques such as laparoscopic repair. This study aims to evaluate the outcomes of surgical management of perforated duodenal ulcers, comparing open and laparoscopic techniques with respect to postoperative complications, hospital stay, recovery time, and mortality. A total of 94 patients admitted to Samarkand State Medical University Hospital between January 2022 and December 2023 with confirmed perforated duodenal ulcer were included in this prospective observational study. Patients were categorized into two groups: Group A underwent open Graham patch repair while Group B underwent laparoscopic repair. Clinical outcomes were analyzed and compared using standardized surgical metrics. Our findings suggest that laparoscopic surgery offers advantages in terms of faster recovery, reduced postoperative pain, and shorter hospital stays, although open surgery remains a reliable option, especially in hemodynamically unstable patients. Perforations in the duodenal wall represent one of the most urgent and life-threatening gastrointestinal conditions, necessitating immediate surgical intervention to prevent systemic infection and death. As medical practice transitions from conventional open procedures to modern minimally invasive methods, evaluating the comparative success of these surgical techniques becomes essential. This clinical review examines surgical outcomes in patients treated for duodenal wall ruptures, analyzing the correlation between intervention types and recovery indicators. It identifies procedural strengths and limitations, offering evidence-based insights to support optimized decision-making in emergency abdominal surgery.